Improving English Speaking Skills at Saba University - Zuheer, Khaled Mohsen Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
This paper is intended to find the possible solutions that may help in improving speaking skills of students at English language and translation programs, through effective strategies during teaching and learning. The paper tried to find out answers to following two questions: a. What are the most important speaking skills for students of English language and translation programs? b. What are the effective strategies and techniques that may participate in improving speaking skills for students of English language and translation programs? Through the analysis of related studies and literature the paper collected the most important strategies, activities and techniques that may help in improving speaking abilities of English language students.
Keywords: speaking skills; strategies; teaching; learning